Labour migration and inclusive development: Setting a course for success - Michelle Leighton (UN Chronicle, 2013)
There are over 100 million migrant workers living and working around the globe. Together with their families they represent most of the international migrants now estimated at 232 million people living outside their country of origin. Almost half are women, migrating increasingly for employment. About one in eight are between the ages of 15 and 24. South-South migration has now surpassed South-North migration: more than 50 per cent of emigrants from developing countries move to another developing country, and largely within their region. Nearly 80 per cent of South- South migration is between countries with a common border.